Glutamine missense suppressor transfer RNAs inhibit polyglutamine aggregation - Rasangi Tennakoon; Teija M.I. Bily; Farah Hasan; Sunidhi Syal; Aaron Voigt; Tugce B. Balci; Kyle S. Hoffman; Patrick O’Donoghue (Molecular Therapy: Nucleic Acids)
Huntington’s disease (HD) is caused by polyglutamine (polyQ) repeat expansions in the huntingtin gene. HD-causative polyQ alleles lead to protein aggregation, which is a prerequisite for disease. Translation fidelity modifies protein aggregation, and several studies suggest that mutating one or two glutamine (Gln) residues in polyQ reduces aggregation. Thus, we hypothesized that missense suppression of Gln codons with other amino acids will reduce polyQ aggregate formation in cells. In neuroblastoma cells, we assessed tRNA variants that misread Gln codons with serine (tRNASerC/UUG) or alanine (tRNAAlaC/UUG). The tRNAs with the CUG anticodon were more effective at suppressing the CAG repeats in polyQ, and serine and alanine mis-incorporation had differential impacts on polyQ. The expression of tRNASerCUG reduced polyQ protein production as well as both soluble and insoluble aggregate formation. In contrast, cells expressing tRNAAlaCUG selectively decreased insoluble polyQ aggregate formation by 2-fold. Mass spectrometry confirmed Ala mis-incorporation at an average level of ∼20% per Gln codon. Cells expressing the missense suppressor tRNAs showed no cytotoxic effects and no defects in growth or global protein synthesis levels. Our findings demonstrate that tRNA-dependent missense suppression of Gln codons is well tolerated in mammalian cells and significantly reduces polyQ levels and aggregates that cause HD.